MODEL ALTERNATIF FILM PENDEK ANIMASI 3D BAGI ANAK-ANAK - Alfan Setyawan (Institut Seni Indonesia Surakarta, 2014)
The article discusses about the form of Sendratari Mahakarya Borobudur (the ballet of Borobudur great work)that is used to be a model in the making of 3D animation short film for children. The problem of research isthe alternative model of 3D animation for children towards Sendratari Mahakarya Borobudur. The researchuses qualitative method. The research data is collected from written sources, art works, key persons, and theaudio video documentation of Sendratari Mahakarya Borobudur. Data is collected by library study, works,observation, interview, and documentation. Data analysis process covers several stages including datacollecting, reduction, data presentation, and summary. Based on the research, it shows that SendratariMahakarya Borobudur is chosen to be an alternative model of 3D animation short film. The story of SendratariMahakarya Borobudur has moral values packed as the alternative model of 3D animation short film andsupposed to have an important role in making the native characteristic in order to become a completelyIndonesian people. The recommended model of 3D animation short film has duration of 15 minutes and it isa story of visual design and storyboard.Keywords: Sendratari (ballet), Mahakarya (great work) Borobudur, 3D animation